MENONTON SINETRON RELIGIUS, MENONTON ISLAM INDONESIA - Muzayin Nazaruddin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
In 2005 – 2007, religious cinemas wrapped with mystique messages were distributed in Indonesian television and reached high rating. How Islam represented in these religious electronic cinemas show the understanding of Islam in Indonesian society these days. So the questions will be answered by this research is: how Islam represented in Indonesian religious electronic cinemas? The approach is semiotica, applied in exlectic ways, combine Saussurean and Peircian traditions. Some research outcomes were resulted. Basically, Islam represented as irational religion, with some signifying practices: 1. Islam looks into world extremely in black and white views, 2. Ideal moslem is a person that full of surrenderness, always (just) pray into Allah, 3. Islamic preachers and Al-Quran represented in reductive ways just as ghost buster, 4. In Islam, death is scarring, God is the cruelest, his torture is horrible, 5. Repent (asking god forgiveness) is an easy and instant process. These religious electronic cinemas reproduce Islamic popular religion, shows diffraction of urban-city views. The main factor is the commercial logic of television.